2005
DOI: 10.17221/5602-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of brucellosis of the European hare in the Czech Republic

Abstract: A geographic information system was used for the analysis of ecological conditions of distribution of natural foci of brucellosis in the European hare (Lepus europaeus) and their long-term persistence in the Czech Republic. The European hare is a reservoir host of Brucella suis biotype 2. A close correlation was found between the geographic distribution and numbers of natural foci of brucellosis in the Czech Republic in 1971 to 1985 and 1986 to 2000 (r = 0.65, n = 814, P = 0.01). Natural foci of brucellosis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…However, the livestock here are predominantly yak and antelope, rather than sheep or goats. These animals are generally farmed by free-range feeding methods, thus minimising human-animal contact [ 36 , 37 ]. Based on the ADL modelling in the four provinces with the severest epidemics of human brucellosis, we showed that the temporal trend of monthly incidence was influenced by temperature and sunshine.…”
Section: Discussionmentioning
confidence: 99%
“…However, the livestock here are predominantly yak and antelope, rather than sheep or goats. These animals are generally farmed by free-range feeding methods, thus minimising human-animal contact [ 36 , 37 ]. Based on the ADL modelling in the four provinces with the severest epidemics of human brucellosis, we showed that the temporal trend of monthly incidence was influenced by temperature and sunshine.…”
Section: Discussionmentioning
confidence: 99%
“…The geographical distribution of biovar 2 has historically occurred in a broad range between Scandinavia and the Balkans. In recent years, several reports of B. suis biovar 2 infections in wild boar and the European hare have been published from the Iberian peninsula (61) to central Europe (73,91).…”
Section: Brucella Suismentioning
confidence: 99%
“…It is accepted that both species play a relevant role as a brucellosis reservoir for domestic pigs, even under natural environmental conditions [3,15,19]. In fact, both wildlife species have been directly involved in the transmission of infection to domestic pigs reared in outdoor farms [10].…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis caused by B. suis biovar 2 is frequently reported in the Eurasian wild boar ( Sus scrofa ) and the European brown hare ( Lepus europaeus ), and apparent prevalence ranging from 8 to 32% has been reported in wild boar in the EU [ 10 , 14 - 18 ]. It is accepted that both species play a relevant role as a brucellosis reservoir for domestic pigs, even under natural environmental conditions [ 3 , 15 , 19 ]. In fact, both wildlife species have been directly involved in the transmission of infection to domestic pigs reared in outdoor farms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%